(untitled) (SCIENCE TIME JOURNAL, 2026)
The necessity for non-Arabic speaking students to study Arabic rhetoric (Balagha)—to comprehend its nuances, experience its secrets, and utilize its communicative power—is no less significant than that of native Arabic speakers. While the objectives of learning are largely identical, non-native students face numerous and more severe challenges in the classroom. Key obstacles include the lack of proficiency among many instructors, the complexity of the scientific material provided, and its lack of suitability for the students’ linguistic level, all of which hinder the learning process.Previous studies have overlooked three critical dimensions: the pedagogical aspect in textbooks and classrooms, the comparative dimension between shared rhetorical styles in Arabic and the students’ mother tongue, and the integration of the four language skills (listening, speaking, reading, and writing) into the teaching of rhetoric. To facilitate the presentation of this noble science, this study addresses these three gaps under the framework of "Contemporary Rhetorical Lessons."